DINAMIKA HUKUM TINDAK PIDANA PENCEMARAN NAMA BAIK - Aprilia, Rizky; Syarifuddin, La; Hamzah, Herdiansyah (Universitas Labuhanbatu, 2025)
The aim of this research is to answer two main points of discussion, namely: first, related to the construction of the meaning of the offense of defamation. Second, the development of regulations for defamation offenses. This research uses a doctrinal approach. The sources of legal material for this research are the Criminal Code, Law Number 11 of 2008 concerning Electronic Information and Transactions, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, and Law Number 19 2024 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which are then analyzed qualitatively. The construction of the meaning of the offense of defamation in the ITE Law focuses on post-amendment, Articles 27A and 27B provide a more detailed definition of defamation. The development of the regulation of defamation offenses in Indonesia shows legal adjustments to technological advances, starting from the Criminal Code which does not cover electronic media to the ITE Law which regulates pollution via digital media. Defamation is regulated in the new Criminal Code in Articles 344 to Article 346 of the new Criminal Code. Existing developments, both the revision of the 2008 to 2024 ITE Law and the new Criminal Code, show a more specific definition and protection of freedom of expression, balancing the protection of individual reputations with the ever-evolving digital reality. Keywords: Dynamics, Defamation, Electronic Media